# How do you solve this system of equation: y = -6 and y = - 2x - 6?

Nov 1, 2017

$\left(x , y\right) = \left(0 , - 6\right)$

#### Explanation:

If
[1]$\textcolor{w h i t e}{\text{XXX}} y = - 6$
and
[2]$\textcolor{w h i t e}{\text{XXX}} y = - 2 x - 6$

Using [1] we can substitute $- 6$ for $y$ in [2]
[3]$\textcolor{w h i t e}{\text{XXX}} - 6 = - 2 x - 6$
then add $6$ to each side
[4]$\textcolor{w h i t e}{\text{XXX}} 0 = - 2 x$
and finally divide both sides by $\left(- 2\right)$
[5]$\textcolor{w h i t e}{\text{XXX")0=xcolor(white)("xxxxxx}}$...or, equivalently, $x = 0$

Nov 1, 2017

$\left(x , y\right) = \left(0 , - 6\right)$

#### Explanation:

color(blue)(rarry=-6 $\left(\text{equation 1}\right)$

color(blue)(rarry=-2x-6 $\left(\text{equation 2}\right)$

As we know that $y = - 6$, we can sub substitute it in equation $2$

$\rightarrow - 6 = - 2 x - 6$

rarr-2x=cancel(-6+6

$\rightarrow - 2 x = 0$

color(green)(rArrx=0

So we can say that

color(purple)((x,y)=(0,-6)

Hope this helps!!! ☺☻